Mitigating fuel tank syndrome pelvic injuries – is there potential for rider worn protectors?. (10th October 2022) - Whyte, Tom; Kent, Nicholas; Cernicchi, Alessandro; Brown, Julie
Abstract: Objective: The aim of this study was to investigate the feasibility of rider-worn pelvis protection for mitigating injury risk when contacting the motorcycle fuel tank in a crash. Methods: A newly developed test apparatus was designed and constructed to simulate the interaction between a rider's pelvis and the motorcycle fuel tank in a frontal crash. Impacts were performed at a velocity of 18 km/h into four motorcycle fuel tanks. Further testing used a rigid fuel tank surrogate and the pelvis surrogate in an unprotected condition and with a series of impact protector prototypes. A subset of prototype samples was also tested at varying tank angles (30°, 37.5°, 45°) and impact speeds (8.5 km/h, 13 km/h, 18 km/h). Analysis of variance was used to determine whether the protector prototypes reduced pelvis response compared to unprotected. Results: Resultant peak pelvis acceleration was reduced by three pelvis impact protector prototypes compared to an unprotected condition. The reduction in peak acceleration occurred without a significant change in the peak pelvis rotational velocity. The pattern of protector performance was consistent at varying fuel tank angles but only reduced the pelvis response at the highest impact speed tested of 18 km/h. Conclusions: The results indicate that there may be potential for using pelvis impact protection to mitigate injury risk by absorbing and/or distributing impact energy that would otherwise be transmitted to the rider's pelvis. However, due to the current paucity in understanding of pelvis biomechanics to anteroposterior loading, it is unknown whether the pelvis acceleration reductions achieved would prevent injury.